The abyss : bridging the divide between Israel and the Arab world - Avidar, Eli (Rowman and Littlefield Publishing, 2015)
Eli Avidar looks into the abyss that divides Israel from its Arab neighbors, in order to understand the inherent flaws, prevailing misunderstandings, and tragic mistakes that characterize the relations and bloodletting, and how, if at all possible, to bridge the differences. In doing so, he offers a new perspective about the reality of the Middle East and all the clichés that have transformed the Hebrew-Arab lexicon into a complex and hopeless minefield. It raises the question of whether the ongoing violent conflict between Israel and its neighbors might also be the result of a serious short c.